Monoclonal antibodies directed against a cell surface-exposed outer membrane protein of Haemophilus influenzae type b. - Robertson, S M (1982)
Monoclonal antibodies directed against several different Haemophilus influenzae type b outer membrane proteins with apparent molecular weights of 45,000, 39,000, and 37,000 were identified by a radioimmunoprecipitation method. Five monoclonal antibodies, including both immunoglobulin G and M isotypes, were specific for the same H. influenzae type b major outer membrane protein (39,000 molecular weight). One of these immunoglobulin G monoclonal antibodies (6A2) was shown to be directed against a cell surface-exposed antigenic determinant of the 39,000-molecular-weight protein, whereas the other monoclonal antibodies directed against this same protein were apparently specific for antigenic determinants not exposed on the H. Influenzae type b cell surface. The cell surface-exposed protein antigenic determinant recognized by monoclonal antibody 6A2 was not unique to the H. influenzae type b strain used as the source of outer membrane vesicles for generating immune spleen cells, but was found in a majority of independently isolated strains of H. influenzae type b. These data indicate that there is antigenic cross-reactivity among H. influenzae type b strains with regard to cell surface-exposed proteins.